Centesimal composition, fatty acids profile and the nutritional quality index of four seafood species from the southern region of Brazil - Isabella Peres Gualda (Acta Scientiarum: Technology, 2018)
The objective of this study was to evaluate the centesimal composition, fatty acid profile and the nutritional quality index of four seafood species: pink shrimp (Penaeus brasiliensis), Pacific white shrimp (Litopenaeus vannamei), mussel (Perna perna) and octopus (Octopus vulgaris), that were collected in Santa Catarina, Brazil. The nutritional quality of the lipid fraction was evaluated by the index of thrombogenicity (IT), index of atherogenicity (IA) and the hypocholesterolaemic fatty acids-to-hypercholesterolaemic fatty acids ratio (h/H). All the studied species presented a high protein content (12.88-21.61%) and a low amount of total lipid (0.26-4.07%). The pink shrimp had the most protein and octopus contained the least total lipid. Eicosapentaenoic acid and docosahexaenoic acid were detected in all samples, presenting the highest values in mussel (204.62 and 123.57 mg 100 g-1, respectively). The analysed species presented low IT and IA values and an h/H ratio around 2 or higher, and therefore, they are considered potentially healthy foods. Moreover, the shrimp species can be classified as a source of omega-3s, while the mussels can be categorised as having a high content in these polyunsaturated fatty acids.